2022
DOI: 10.5897/ajar2022.15985
|View full text |Cite
|
Sign up to set email alerts
|

Survey of fungal diseases associated with amaranth (Amaranthus species) in peri-urban vegetable farms in Kumasi and Tamale metropolis of Ghana

Abstract: Amaranthus species is an important leafy vegetable in Ghana; however, foliar diseases of the crop reduce the marketable and edible portions as well as income to farmers. To facilitate the development of disease management strategy, there is the need to document various diseases limiting amaranth production. In view of this, surveys were carried out in forty-three peri-urban vegetable farms in the Kumasi and Tamale Metropolis of Ghana to assess the prevalence and severity of fungal diseases associated with amar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…Pythium stem canker was recorded in all accessions studied except NGRCO 6977. Zippora et al [42], surveyed in Ghana and found incidence percentage of anthracnose ranging from 0 to 58.3% in amaranth, quite similar to our result. Celine et al [43] also reported high attack of Rhizoctonia solani on amaranth accessions.…”
Section: Disease Evaluation Of Amaranthus Accessionssupporting
confidence: 91%
“…Pythium stem canker was recorded in all accessions studied except NGRCO 6977. Zippora et al [42], surveyed in Ghana and found incidence percentage of anthracnose ranging from 0 to 58.3% in amaranth, quite similar to our result. Celine et al [43] also reported high attack of Rhizoctonia solani on amaranth accessions.…”
Section: Disease Evaluation Of Amaranthus Accessionssupporting
confidence: 91%
“…38 The three most common and often reported diseases of the amaranth crop in the nation are anthracnose, damping-off, and wet rot. 39 Similarly, postharvest losses of amaranth continue to be a major issue for the security of food and nutrition in sub-Saharan Africa, particularly Ethiopia. 40 Therefore, it is projected that 15.5 to 27.2% of the amaranth crop is wasted each year as a result of inadequate postharvest facilities in the nation.…”
Section: Factors Affecting Amaranth Production In Ethiopiamentioning
confidence: 99%